Strategy as leadership : facing adaptive challenges in organizations - Vassolo, Roberto; Weisz, Natalia (Stanford Business Books, an imprint of Stanford University Press, 2022)
Strategy as Leadership is about making sense of predictable but drastic changes that can alter the relationship between businesses and their competition, posing substantial leadership challenges to senior management teams. Roberto S. Vassolo and Natalia Weisz provide a framework to address and respond to these critical changes by identifying them, describing the inner tensions these changes generate, and providing guidance for their successful navigation. This outside-in approach specifies the salient leadership challenges that executives will face while mobilizing their organizations to respond effectively to competitive and environmental change. This book claims that strategy is leadership as, in this framework, these environmental changes demand shifts in strategic priorities that result in a consistent pattern of resistance. If we know that changes are occurring in the competitive environment, we can soon identify who will be most resistant to the shift in priorities necessary to address the new situation. This book is for senior management teams to enable their organizations' capabilities to adapt and address environmental changes successfully.
Keywords: Strategic planning.; Leadership.; Organizational change.; Leadership; Organizational Innovation; Planification stratégique.; Changement organisationnel.; BUSINESS & ECONOMICS / Strategic Planning.; Organizational change; Strategic planning; Economics; Business & Economics